Assistance of Students in Christian Religious Education to Increase Learning Motivation at Benih Pengharapan Elementary School, Lembang, West Java - Sitorus, Ricky Ivan Kristian; Tanasyah, Yusak (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2023)
Education is a conscious and planned effort to create a learning atmosphere, and even a learning process, so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills. Christian Religious Education to educate him. Student assistance is something that already has good personal quality standards, responsibility, independence and even discipline. So don't be surprised a student mentoring must also be able to provide and instill it all, so that it can motivate students personally, even equip students through various needs, and grow in Jesus Christ. Assistance to PAK teachers must also be able to become creative coordinators in increasing the motivation of students in each lesson, because most of it is in the surrounding environment such as schools and homes, it can affect students to become lazy in learning, so they cannot be motivated in participating in learning. The main objective of this research is to assist students in Christian Religious Education to increase their motivation to study at Benih Pengharapan Elementary School, Lembang, West Java. Pendidikan merupakan usaha sadar dan terencana untuk mewujudkan suasana belajar, dan bahkan proses pembelajaran, agar peserta didik secara aktif mengembangkan potensi dirinya untuk memiliki kekuatan spiritual keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia, dan keterampilan, maka dari sini perlulah pendampingan pada pelajaran Pendidikan Agama Kristen untuk mendidiknya. Pendampingan peserta didik menjadi suatu hal yang sudah memiliki standar kualitas pribadi yang baik, tanggung jawab, mandiri dan bahkan disiplin. Maka jangan heran seorang pendampingan peserta didik juga harus bisa memberikan dan menanamkan itu semua, agar bisa memotivasikan peserta didik dalam pribadinya, bahkan memperlengkapi peserta didik melalui berbagai kebutuhan, dan bertumbuh di dalam Yesus Kristus. Pendampingan kepada Guru PAK juga harus bisa menjadi koordinator yang kreatif dalam meningkatkan motivasi peserta didik setiap pembelajaran, sebab karena sebagian besar di lingkungan sekitarnya seperti sekolah, dan rumah, bisa mempengaruhi peserta didik menjadi malas belajar, sehingga tidak bisa motivasi dalam mengikuti pembelajaran. Tujuan utama dalam penelitian ini adalah pendampingan peserta didik dalam Pendidikan Agama Kristen untuk meningkatkan motivasi belajar di Sekolah Dasar Benih Pengharapan, Lembang, Jawa Barat.